Manajemen pembelajaran guru seni di SMK Negeri 5 Yogyakarta - Mustofa, Ari; Khodijah, Khodijah (Rafandha Press, 2024)
Purpose: This research aims to explore and analyze learning management carried out by art teachers at Vocational High School (SMK) 5 Yogyakarta. The main focus of this research is to identify effective learning management strategies, which consist of planning and implementing learning carried out by art teachers at the school. Method: This research is qualitative. Subjects of this study were art teachers of ceramics crafts, wooden crafts, and metal crafts at SMK Negeri 5 Yogyakarta. Determination of the subject is done by random sampling, which consists of 3 teachers and the object of research is the effectiveness of art teachers learning process. Data was obtained using observation, interviews, and documentation, as descriptive analysis. Findings: The results of descriptive research reveal that art teacher learning at SMK Negeri 5 Yogyakarta is viewed from the aspects of learning planning and learning implementation. Learning planning activities carried out by teachers have been realized in the form of a syllabus and lesson plans. Teacher learning activities at SMK Negeri 5 Yogyakarta go through three stages, namely preliminary activities, core activities and closing activities. The learning carried out by the teacher was declared successful as proven by the students' work with good work in terms of creativity, beauty, form and completion of the final result. Evaluation of learning by teachers is realized by scoring in the form of numbers based on minimum completeness criteria.